BPKP's Authority in Supervising the Activities of the State General Treasurer and Its Implications for State Financial Accountability - Puspita Dewi Putri; Uyan Wiryadi; Teguh Satya Bhakti (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study analyzes the construction of authority in the state financial management and supervision system, focusing on the position of the Minister of Finance as the State General Treasurer (BUN) and the authority of the Financial and Development Supervisory Agency (BPKP) in supervising BUN activities. In the country's financial legal system, the President holds the power to manage state finances, the implementation of which is delegated to the Minister of Finance based on laws and regulations. This position places the Minister of Finance as the holder of the general treasury function who is responsible for the management of the state treasury, the implementation of fiscal functions, as well as the guarantee of administrative order and state financial accountability. Legal problems arise related to the basis and character of BPKP's authority in supervising BUN, especially from the perspective of authority theory. This study uses normative legal research methods with legislative and conceptual approaches to analyze the sources of authority and the implications of legal accountability. The results of the study show that the authority of the Minister of Finance as a BUN has a clear normative basis and is attached to the position, thus bringing the consequences of full administrative accountability. Meanwhile, the authority of the BPKP to supervise BUN activities is more appropriately qualified as a presidential mandate within the framework of the government's internal control system. In the construction of the mandate, there is no transfer of responsibility, so the highest constitutional and political responsibility remains with the President. The clarity of the construction of authority is important to ensure legal certainty, prevent overlapping functions, and strengthen accountability in state financial management.